DAYA KEKUATAN TAWAR MENAWAR PENGUSAHA SLONDOK DI DESA SUMURARUM KECAMATAN GRABAG KABUPATEN MAGELANG - Ruth Manimabi; Sony Heru Priyanto; Hendrik Johannes Nadapdap (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2018)
ABSTRACT- This study aims to examine the external environment of slondok companies related to bargaining power used by slondok entrepreneurs with 2 Porter powers, namely bargaining power of buyers and suppliers as well as alternative strategies used by slondok entrepreneurs in increasing bargaining power of slondok. The type of research used is descriptive qualitative. The research method used is case study. The data used are primary and secondary data. Methods of data collection by interview. Participant selection technique with purposive sampling. Validity test and reliability test using source triangulation. Based on the results of research related to the strength of Porter in slondok company shows that the bargaining power of buyers is high, the bargaining power of the suppliers is as well as the alternative strategy applied is Porter's generic strategy. Kata kunci-agroindustri; industri kecil; kekuatan Porter; strategi generik